Late‐onset argininosuccinic aciduria in a 72‐year‐old man presenting with fatal hyperammonemia. Issue 1 (26th September 2021) - Leuger, Laurent; Dieu, Xavier; Chao de la Barca, Juan Manuel; Moriconi, Mikael; Halley, Guillaume; Donin de Rosière, Xavier; Reynier, Pascal; Mirebeau‐Prunier, Delphine; Homedan, Chadi
Abstract: Argininosuccinate lyase deficiency (ASLD, MIM # 207900) is an inherited urea cycle disorder. There are mainly two clinical forms, an acute neonatal form which manifests as life‐threatening hyperammonemia, and a late‐onset form characterised by polymorphic neuro‐cognitive or psychiatric presentation with transient hyperammonemia episodes. Here, we report a late‐onset case of ASLD in a 72‐year‐old man carrying a homozygous pathogenic variant in the exon 16 of the ASL gene, presenting for the first time with fatal hyperammonemic coma. This case report shows the need to systematically carry out an ammonia assay when faced with an unexplained coma.